Modulation of 7 T fMRI Signal in the Cerebellar Cortex and Nuclei During Acquisition, Extinction, and Reacquisition of Conditioned Eyeblink Responses - Ernst, Thomas M.; Thürling, Markus; Müller, Sarah; Kahl, Fabian; Maderwald, Stefan; Schlamann, Marc; Boele, Henk‐Jan; Koekkoek, Sebastiaan K. E.; Diedrichsen, Jörn; De Zeeuw, Chris I.; Ladd, Mark E.; Timmann, Dagmar (Human brain mapping, 2017)
Classical delay eyeblink conditioning is likely the most commonly used paradigm to study cerebellar learning. As yet, few studies have focused on extinction and savings of conditioned eyeblink responses (CRs). Saving effects, which are reflected in a reacquisition after extinction that is faster than the initial acquisition, suggest that learned associations are at least partly preserved during extinction. In this study, we tested the hypothesis that acquisition‐related plasticity is nihilated during extinction in the cerebellar cortex, but retained in the cerebellar nuclei, allowing for faster reacquisition. Changes of 7 T functional magnetic resonance imaging (fMRI) signals were investigated in the cerebellar cortex and nuclei of young and healthy human subjects. Main effects of acquisition, extinction, and reacquisition against rest were calculated in conditioned stimulus‐only trials. First‐level β values were determined for a spherical region of interest (ROI) around the acquisition peak voxel in lobule VI, and dentate and interposed nuclei ipsilateral to the unconditioned stimulus. In the cerebellar cortex and nuclei, fMRI signals were significantly lower in extinction compared to acquisition and reacquisition, but not significantly different between acquisition and reacquisition. These findings are consistent with the theory of bidirectional learning in both the cerebellar cortex and nuclei. It cannot explain, however, why conditioned responses reappear almost immediately in reacquisition following extinction. Although the present data do not exclude that part of the initial memory remains in the cerebellum in extinction, future studies should also explore changes in extracerebellar regions as a potential substrate of saving effects. Hum Brain Mapp 38:3957–3974, 2017. © 2017 Wiley Periodicals, Inc.